1997
DOI: 10.1111/j.1365-2109.1997.tb01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Escherichia coli in the intestine of fish

Abstract: Establishment and persistence of Escherichia coli in the intestine of rainbow trout. Oncorhynchus mykiss (Walbaum), was investigated. Infection was achieved by ingestion of contaminated feed but not by bath exposure. At 1 5°C, E. coli was found to increase in number in the intestine offish after an initial decline, and could still be detected after 4 days. At 6°C it was detected for 2 days but the numbers declined steadily. A similar trend was observed when extracted gut content was inoculated with E. coli in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 32 publications
(27 reference statements)
0
8
0
Order By: Relevance
“…, 1990). Other studies showed that E. coli can establish and persist for a few days in fish intestines, giving them the opportunity to spread to distant waters (Rio‐Rodriguez et al. , 1997; Guzmán et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 1990). Other studies showed that E. coli can establish and persist for a few days in fish intestines, giving them the opportunity to spread to distant waters (Rio‐Rodriguez et al. , 1997; Guzmán et al.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a farm environment, from the inoculation of a cow, a strain can be recovered from caretakers, mice, pigs, fowls and flies in a few days ( Marshall et al , 1990 ). Other studies showed that E. coli can establish and persist for a few days in fish intestines, giving them the opportunity to spread to distant waters ( Rio-Rodriguez et al , 1997 ; Guzmán et al , 2004 ). Therefore, the continuous variations in metabolic phenotypes can also reflect the adaptation to past niches.…”
Section: Discussionmentioning
confidence: 99%
“…salmonicida in Atlantic salmon (Salmo salar L.) in vitro. Additionally, E. coli in the intestine are pathogens with the particular potential of causing enteric infection (Rio-Rodriguez et al 1997). These intestinal microflora are sensitive to dietary changes (Ringø & Birkbeck 1999).…”
Section: As Shown Inmentioning
confidence: 99%
“…Although the chances are most probably minimal, other bacteria can theoretically take up the vaccine plasmid. However, E. coli, the most likely organism that could be implicated in transmitting the plasmid outside the target species, is not considered a natural component of the gut flora of salmonids under culture conditions (14) and is absent from the intestinal content of cultured fishes (25). In order to achieve the highest possible level of precaution, DNA vaccine plasmids for fish should be limited to include only the strictly necessary genes and regulatory elements, and be devoid of gene elements such as genes that mediate resistance to important antibiotics.…”
Section: Regulation Of Veterinary Dna Vaccinesmentioning
confidence: 99%